2020
DOI: 10.1016/j.tics.2020.09.002
|View full text |Cite|
|
Sign up to set email alerts
|

Artificial Intelligence and the Common Sense of Animals

Abstract: The problem of common sense remains a major obstacle to progress in artificial intelligence. Here, we argue that common sense in humans is founded on a set of basic capacities that are possessed by many other animals, capacities pertaining to the understanding of objects, space, and causality. The field of animal cognition has developed numerous experimental protocols for studying these capacities and, thanks to progress in deep reinforcement learning (RL), it is now possible to apply these methods directly to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…In other words, it is what we can do with objects that matter, not how they look. Shanahan et al (2020) discuss this problem. As an example, they take the concept of a "container" that is central to much human interaction with the world.…”
Section: Eventsmentioning
confidence: 98%
See 1 more Smart Citation
“…In other words, it is what we can do with objects that matter, not how they look. Shanahan et al (2020) discuss this problem. As an example, they take the concept of a "container" that is central to much human interaction with the world.…”
Section: Eventsmentioning
confidence: 98%
“…The appearance of containers can vary widely, but it is their affordances that are crucial for how we interact with them. There seems to be no good model of how to capture the affordances of objects from, say, a video stream (Shanahan et al, 2020). As regards actions, they are understudied in robotics.…”
Section: Eventsmentioning
confidence: 99%
“…model on which most AI research is based, this precondition of intelligent behavior necessarily appears to AI researchers as the need to find "a formal representation in which all the knowledge and beliefs of an average adult human being can be made explicit and organized for flexible use". While it suffices for our purposes to note that endowing computational technology with common sense remains one of the biggest challenges in the field of AI (Shanahan et al, 2020;Mitchell, 2021), the arguments presented by Dreyfus (1992) cast doubt on whether a satisfactory formalization of common-sense knowledge can ever be achieved.…”
Section: What Robots Cannot Do (Yet)mentioning
confidence: 98%
“…Endowing robots and other computer-based systems with folk psychology requires solving a more general problem that computer science has so far been unable to solve: the common-sense problem in artificial intelligence (AI) research (McCarthy, 1960;Davis & Marcus, 2015;Lake, Ullman, Tenenbaum, & Gershman, 2017;Shanahan, Crosby, Beyret, & Cheke, 2020;Levesque, 2017). As argued by Dreyfus in his 1992 book What Computers Still Can't Do, "Intelligence requires understanding, and understanding requires giving a computer the background of common sense that adult human beings have by virtue of having bodies, interacting skillfully with the material world, and being trained into a culture. "…”
Section: What Robots Cannot Do (Yet)mentioning
confidence: 99%
“…6-29-2 was a variant of L1 basic navigation tasks but with colourings of the walls, roof, and floor altered. A suggestion for why the AIs performed considerably worse than the children in the L6 tasks, and compared to their performances in comparable levels (e.g., L1, L2, and L4) is that the AIs used perceptual cues of colour or shape to perform successfully, whereas children are capable of abstracting beyond those cues to more features pertaining to objecthood (see Dubey et al 2018;Shanahan et al 2020). However, post hoc analyses showed that performance on 6-29-2 and the analogous task 1-4-3 were significantly different, as were performances on 3-11-1 compared to 6-12-2.…”
Section: Comparing Performance On Specific Cognitive Abilitiesmentioning
confidence: 99%